Different optical properties in different periodic slot cavity geometrical morphologies - 周静 沈萌 杜澜 邓彩松 倪海彬 王鸣 (Chinese physics B, 2016)
In this paper,optical properties of two-dimensional periodic annular slot cavity arrays in hexagonal close-packing on a silica substrate are theoretically characterized by finite difference time domain（FDTD） simulation method.By simulating reflectance spectra,electric field distribution,and charge distribution,we confirm that multiple cylindrical surface plasmon resonances can be excited in annular inclined slot cavities by linearly polarized light,in which the four reflectance dips are attributed to Fabry–Perot cavity resonances in the coaxial cavity.A coaxial waveguide mode TE11 will exist in these annular cavities,and the wavelengths of these reflectance dips are effectively tailored by changing the geometrical pattern of slot cavity and the dielectric materials filled in the cavities.These resonant wavelengths are localized in annular cavities with large electric field enhancement and dissipate gradually due to metal loss.The formation of an absorption peak can be explained from the aspect of phase matching conditions.We observed that the proposed structure can be tuned over the broad spectral range of 600–4000 nm by changing the outer and inner radii of the annular gaps,gap surface topography.Meanwhile,different lengths of the cavity may cause the shift of resonance dips.Also,we study the field enhancement at different vertical locations of the slit.In addition,dielectric materials filling in the annular gaps will result in a shift of the resonance wavelengths,which make the annular cavities good candidates for refractive index sensors.The refractive index sensitivity of annular cavities can also be tuned by the geometry size and the media around the cavity.Annular cavities with novel applications can be implied as surface enhanced Raman spectra substrates,refractive index sensors,nano-lasers,and optical trappers.